The Interplay Between Childhood Sexual Abuse, Self-Concept Clarity, and Dissociation: A Resilience-Based Perspective - Lassri, Dana (Journal of interpersonal violence, 2023)
Background: Despite a robust consensus regarding the potentially negative implications of childhood sexual abuse (CSA), research investigating risk and protective factors—particularly among well-functioning young adults—is scant. Dissociation is one of the major maladaptive outcomes of CSA. Nevertheless, CSA explains only about 10% of the variance of dissociation. Possibly, this modest effect size is due to protective factors moderating the relation between CSA and dissociative symptoms. One such factor may be the extent to which one has succeeded in developing a clear and coherent sense of who they are. Objective: We aimed to explore whether self-concept clarity (SCC) moderates the relationship between CSA and dissociation (Model 1), and an alternative hypothesis, whereby CSA may moderate the relationship between SCC and dissociation (Model 2). Participants and Setting: This was tested among 65 well-functioning young women drawn from an earlier study that intentionally oversampled CSA survivors. Methods: We included data from survivors of CSA by a known perpetrator (n = 35) and women with no sexual trauma (n = 30). Results: Findings were consistent with both Model 1 and Model 2, but only when depersonalization-derealization, namely detachment, was considered. Simple effects analyses revealed that CSA was related to depersonalization-derealization only under low SCC levels (Model 1), and SCC was negatively related to depersonalization-derealization only in the CSA group (Model 2). Conclusions: Findings suggest that SCC is a protective factor, buffering the association between CSA and detachment (depersonalization-derealization) symptoms. Clinical implications are discussed.